The impact of climate change on agriculture in the Republic of Mauritius - Jönsson, Madeleine (2011)
"Food security is a situation that exists when all people, at all times, have physical and economic access to sufficient, safe and nutritious food that meets their dietary needs and food preferences for an active and healthy life" (FAO Summit, 2003, pp. 28).